Can snakes use yolk reserves to maximize body size at hatching?. Issue 6 (27th December 2018) - Qu, Yan-Fu; Zhao, Shu-Zhan; Jiang, Xu-Fei; Lin, Long-Hui; Ji, Xiang
Abstract: We experimentally miniaturized freshly laid eggs of the Chinese cobra Naja atra (Elapidae) by removing ∼10% and ∼20% of original yolk. We tested if yolk-reduced eggs would produce 1) normal-sized hatchlings with invariant yolk-free body mass (and thus invariant linear size) but dramatically reduced or even completely depleted residual yolk, 2) smaller hatchlings with normal-sized residual yolk but reduced yolk-free body mass, or 3) smaller hatchlings of which both yolk-free body mass and residual yolk are proportionally reduced. Yolk quantity affected hatchling linear size (both snout-vent length and tail length) and body mass. However, changes in yolk quantity did not affect incubation length or any hatchling trait examined after accounting for egg mass at laying (for control and sham-manipulated eggs) or after yolk removal (for manipulated eggs). Specifically, yolk-reduced eggs produced hatchlings of which all major components (carcass, residual yolk, and fat bodies) were scaled down proportionally. We show that snakes cannot use yolk reserves to maximize their body size at hatching. Furthermore, our data also suggest that the partitioning of yolk in embryonic snakes is species-specific.